Peran Modal Sosial dalam Membangun Jejaring Pemasaran Formalin Nabati dari Tanaman Lamtoro Berbasis Kelompok Tani (Kasus di Kelompok Tani Werdi Gopala Desa Pucaksari, Kecamatan Busungbiu, Kabupaten Buleleng, Bali) - PRATIWI AD, NI KETUT GAYATRI ADE; SUDARTA, WAYAN; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The role of social capital in the Werdi Gopala Farmer Group has not been maximally carried out in developing the network of plant formalin marketing, so it needs to be studied by using trust, social network, social norm, and cooperation. The purpose was to determine the role of social capital in building a marketing network of formalin of lamtoro plant and to find out the obstacles encountered in plant formalin market. This research was conducted in the Pucaksari Village, Busungbiu Sub-District, Buleleng Regency, Bali. The findings showed that the role of social capital in establishing farmer group-based marketing network of plant formalin in the case of Werdi Gopala Farmer Group of Pucaksari Village is classified in the medium category. The role of each indicator of social capital is the role of trust classified in good category. The role of social networks is categorized very poor. The role of social norms is classified as moderate category. The role of cooperation is classified as moderate category. The main obstacle faced by the farmer group in marketing plant formalin is technical aspect which covers condition of equipment that is not productive. The second constraint is from the economic aspect which includes the lack of capital to purchase the equipment used to produce plant formalin, and the absence of plant formalin marketing from the farmer group. Suggestions that can be given is that by improving social network by coaching farmer group to use printed media and social media to market formalin plant assisted by the agricultural extension or students in their community service in Pucaksari Village, increasing cooperation with company in agriculture, adding equipments to produce formalin plant and increasing the capital by submitting a proposal to the government to get equipments or capital aids.